Research and Establishment of UHV AC Transmission Model - Yang, Hao; Tang, Fei (Applied Mechanics and Materials, 2015)
There is different applicable transmission capacity and range between 1000kV and 500kV AC transmission. The traditional method is to use the continuous power flow algorithm by BPA simulation software. But this method is complicated and time-consuming. Calculation is particularly large when electricity has a variety of power demand analysis. This paper presents an algorithm based on the AC line transmission capacity, using MATLAB software programming to achieve the establishment of UHV AC transmission model and economical optimization strategy. The method can use thermal limit, voltage limit, landing stability constraints to get the AC line transmission capacity curve by considering the factor of power network strength. On the basis of this method, an UHV AC transmission model can be built combining with unit capacity annual cost algorithm, which can meet the power transmission of arbitrary transmission capacity and the optimal economic of any transmission distance, has an important reference significance and practical value for the planning and construction of electric transmission lines in China.